THE ASSISTENCE AND PERFORMANCE EVALUATION OF THE WORKFORCE FACILITATOR PROGRAM OF INHABITABLE HOUSING IN TANGERANG DISTRICT - Puro, Sarjono; Maria, Kiki; Manurung, Edison H.; Naibaho, Pio Ranap Tua; Imanto, Yuwono (International Journal of Engagement and Empowerment (IJE2), 2025)
The Tangerang Regency Housing, Settlement and Cemetery Service (DPPP) supports regional performance achievements in improving environmental management for sustainable development, especially in the residential infrastructure sector. The 2024 RTLH Program, still the Tangerang Regency's Leading Program in the Sub-districts, aims to help people living in houses whose conditions do not meet health and safety standards. The impact of RLTH on residents/recipients of assistance includes social and economic effects. The role of all parties is vital, and the community's increased participation in the successful development that has been implemented can be felt by the community in developing Tangerang Regency. One of the roles in the success of the RTLH program in Tangerang Regency is the Field Facilitator (TFL), who collaborates with experts, both technical and empowerment, and the RTLH Community Forum (Formas) to improve RTLH development. TFL assistance and evaluation are for DPPP recommendations on TFL performance. The method of implementing evaluation activities uses several techniques, namely observation, interviews, discussions, written tests and documentation. From the evaluation results carried out by experts and representatives of the Tangerang Regency DPPP, it was found that 4 (four) TFL workers out of 23 TFLs were absent and received the lowest score. TFLs who are absent are deemed not to have committed to carrying out the duties and responsibilities that have been determined and agreed upon.